First record of the large-headed goby, Millerigobius macrocephalus (Actinopterygii: Perciformes: Gobiidae), from Italy - S. Giacobbe; A. Spinelli; S. De Matteo; M. Kovačić (Acta Ichthyologica et Piscatoria, 2016)
Two confined populations of an inadequately known gobiid, Millerigobius macrocephalus (KolombatoviÄ‡, 1891), new species for Italy, have been reported for the protected areas of â€śCapo Peloro Lagoonâ€ť and â€śMarinello Lakesâ€ť, NE Sicily. The specimens found were described and illustrated. Additional data were provided on the habitat preferences of this fish species. The authors emphasize the need for biodiversity inventories of inadequately studied Mediterranean lagoons.